2011
DOI: 10.3758/s13428-011-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Introducing LexTALE: A quick and valid Lexical Test for Advanced Learners of English

Abstract: The increasing number of experimental studies on second language (L2) processing, frequently with English as the L2, calls for a practical and valid measure of English vocabulary knowledge and proficiency. In a large-scale study with Dutch and Korean speakers of L2 English, we tested whether LexTALE, a 5-min vocabulary test, is a valid predictor of English vocabulary knowledge and, possibly, even of general English proficiency. Furthermore, the validity of LexTALE was compared with that of self-ratings of prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
970
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 947 publications
(993 citation statements)
references
References 52 publications
16
970
0
7
Order By: Relevance
“…The results of these ratings, given on a scale from one to seven, are summarised in Table 1. Participants were also tested for their Dutch vocabulary knowledge using the Dutch version of LexTALE, a short non-speeded lexical decision task on pseudowords and infrequent words (which is validated only for English so far; Lemhöfer & Broersma, 2012). The mean score (a percentage-correct measure adjusted for yes-or no-bias) was 72.6 (minimum 55.0, maximum 85.5, SD = 8.2), which, in English, would roughly correspond to the Common European Framework of Reference for Languages (CEF) proficiency level B2 (Upper intermediate).…”
Section: Methodsmentioning
confidence: 99%
“…The results of these ratings, given on a scale from one to seven, are summarised in Table 1. Participants were also tested for their Dutch vocabulary knowledge using the Dutch version of LexTALE, a short non-speeded lexical decision task on pseudowords and infrequent words (which is validated only for English so far; Lemhöfer & Broersma, 2012). The mean score (a percentage-correct measure adjusted for yes-or no-bias) was 72.6 (minimum 55.0, maximum 85.5, SD = 8.2), which, in English, would roughly correspond to the Common European Framework of Reference for Languages (CEF) proficiency level B2 (Upper intermediate).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain an indication of individual proficiency in English, we administered four additional tests: (1) a questionnaire requesting the participants to write down the English names of all the pictures used throughout the experiment, which allowed us to individually assess which of the L2 translations were known by the participants; (2) a multiple-choice grammar test (adapted from http://www.transparent. com/learn-english/proficiency-test.html), which required the completion of ten sentences with the correct grammatical form; (3) a multiple-choice reading comprehension test derived from the same source, which required answering questions about short paragraphs of text; and (4) the LexTALE (Lemhöfer & Broersma, 2012) to estimate vocabulary size. Additionally, we administered a language background questionnaire which collected self-reported information on the daily use of English, self-ratings with respect to reading, listening, writing, and speaking proficiency, and the degree of immersion (see Appendix C for a summary of the results across experiments).…”
Section: Participantsmentioning
confidence: 99%
“…Only participants who scored at least at the 75 th centile (more than 17 correct answers) on the test were included in the study and considered relatively skilled readers, and the two groups were matched according to the raw scores (deaf: mean=21.90, SD=3.08, range=18-27; hearing: mean=23.70, SD=3.25, range=17-27). All the participants also completed the Spanish version of LexTALE (Izura, Cuetos, & Brysbaert, 2014), a lexical decision test comprising 60 real words and 30 nonwords that provides a good estimate of language knowledge (e.g., de Bruin, Carreiras, & Duñabeitia, 2017;Lemhöfer & Broersma, 2012). The final scores (in percentages) showed that both groups completed the test accurately, demonstrating a high language knowledge and no differences among the groups (deaf: mean=91.16, SD=13.22;hearing: mean=95.66,SD=3.43;p=.22)…”
Section: Participantsmentioning
confidence: 99%